Successful generating factors for knowledge management through the application of a structural equation model - Romero González, Rosa María (2019)
The purpose was to analyze how the transfer of knowledge is managed in an institution of higher education by analyzing a model of structural equations. The research was conducted on the basis proposed by Molina and Marsal (2002) model, analyzing the implication of the high direction, organizational culture, management skills, technology, knowledge management processes and indicators. The questionnaire consisted of 34 questions in Likert scale. Cronbach’s alpha coefficient obtained for the six variables was .948. It was noted that managers integrate and support knowledge management; participants are considered responsible for their own information. The influence of the observed variables in the variable under study was identified through analysis of a structural equation model.